2013
DOI: 10.1002/wcc.245
|View full text |Cite
|
Sign up to set email alerts
|

Climate policy and the ‘carbon haven’ effect

Abstract: International audienceIn a world with uneven climate policies, the carbon price differentials across regions could shift the production of energy-intensive goods from carbon-constrained countries to " carbon havens " , or countries with laxer climate policy. This would reduce the environmental benefits of the policy (carbon leakage) while potentially damaging the economy (competitiveness concerns). A review on these questions is provided in this article. First we discuss the main terms involved such as carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 137 publications
3
46
0
Order By: Relevance
“…Full auctioning for the cement sector would be the first best solution, but it is politically hard to achieve and presents some risks of carbon leakage in case of high carbon price (Dröge, 2009). Border carbon adjustments (BCAs), the secondbest option, could partially avoid carbon leakage 37 and restore competitiveness so as to allow full auctioning; but their compatibility with the World Trade Organization and their political acceptability at the international level is very challenging (Branger and Quirion, 2014a). Output-based allocations, especially based on a combined clinker and clinker-to-cement ratio benchmarking, would then represent a third-best solution, inducing less economic distortions and more incentive to reduce carbon emissions than the current allocation methodology.…”
Section: Resultsmentioning
confidence: 99%
“…Full auctioning for the cement sector would be the first best solution, but it is politically hard to achieve and presents some risks of carbon leakage in case of high carbon price (Dröge, 2009). Border carbon adjustments (BCAs), the secondbest option, could partially avoid carbon leakage 37 and restore competitiveness so as to allow full auctioning; but their compatibility with the World Trade Organization and their political acceptability at the international level is very challenging (Branger and Quirion, 2014a). Output-based allocations, especially based on a combined clinker and clinker-to-cement ratio benchmarking, would then represent a third-best solution, inducing less economic distortions and more incentive to reduce carbon emissions than the current allocation methodology.…”
Section: Resultsmentioning
confidence: 99%
“…The threat of carbon leakage is rarely significant in an economy-wide 6 sense (Barker et al 2007;Zhou et al 2010). A review by Branger and Quirion (2014) of ex-post econometric studies observed that no study has found any statistically significant sign of carbon leakage. More specific studies, particularly on the EU ETS, have confirmed this in regard to both leakage (Branger et al 2013;Reinaud 2008) and loss of competitiveness (Anger and Oberndorfer 2008;Demailly and Quirion 2008).…”
Section: Effectiveness: Critical Mass Governancementioning
confidence: 93%
“…Although there is no evidence that climate policy does indeed cause firms to relocate to unregulated countries (Branger and Quirion 2014), the potential job loss in energy intensive industries is a concern to decision makers. Just in case there really is a threat to jobs in the energy intensive industry, several options to avoid the job loss are available.…”
Section: Climate Policy Can Be Combined With Smart Industrial Policy mentioning
confidence: 99%